1990
DOI: 10.1111/j.1398-9995.1990.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of IgG subclass antibodies to wheat flour antigens in bakers

Abstract: We measured the IgG subclass antibody levels to wheat flour in 42 bakers and 20 controls with an enzyme immunoassay. The levels of total IgG, IgG1 IgG2 and IgG4 antibodies were significantly higher in the bakers than in the unexposed controls. The presence of anti-wheat flour IgG subclass antibodies in the bakers was correlated with various clinical variables including IgE levels, duration of asthmatic or rhinitis symptoms, skin prick test response, peripheral blood eosinophil levels, bronchial histamine react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
6
14
0
1
Order By: Relevance
“…The data show a more significant association of HDI-specific IgG titers (elevated in 36% of painters) with exposure than limited previous human studies. 32,38,43 The findings are consistent with studies of workers exposed to other isocyanates such as diphenylmethane diisocyanate 44,45 as well as known asthma-causing agents such as anhydrides, rat, or wheat flour antigens, [46][47][48] in which specific IgG responses have tended to correlate with exposure. The significant association between vapor HDIexposed albumin-specific serum IgG titers and exposure suggests that this biomarker may be useful in targeting and monitoring industrial hygiene practices.…”
Section: Discussionsupporting
confidence: 88%
“…The data show a more significant association of HDI-specific IgG titers (elevated in 36% of painters) with exposure than limited previous human studies. 32,38,43 The findings are consistent with studies of workers exposed to other isocyanates such as diphenylmethane diisocyanate 44,45 as well as known asthma-causing agents such as anhydrides, rat, or wheat flour antigens, [46][47][48] in which specific IgG responses have tended to correlate with exposure. The significant association between vapor HDIexposed albumin-specific serum IgG titers and exposure suggests that this biomarker may be useful in targeting and monitoring industrial hygiene practices.…”
Section: Discussionsupporting
confidence: 88%
“…Only one study [98] has documented an association between the presence of specific IgG 4 against phthalic anhydride and work-related asthma, while specific IgG antibodies correlated with the level of workplace exposure. Investigation of specific IgG and IgG 4 in workers exposed to HMW agents provided broadly similar results, since the levels of these antibodies correlated with estimates of exposure to rat allergens [100], wheat flour [101] and grain dust [102], but not with the presence of workrelated symptoms. There was an association between specific IgG and/or IgG 4 antibodies and specific IgE among workers exposed to reactive dyes [103], citrus red mite [104] and grain dust [102].…”
Section: Specific Immunoglobulin G Antibodiessupporting
confidence: 63%
“…This study further demonstrated that IgG4 responses develop prior to IgE responses and responses remained stable over time 13. Studies among bakery workers by Tiikkainen and Klockars24 suggested that the levels of IgG and IgG subclasses to wheat flour in bakers reflected exposure, but were not related to any specific clinical situation. Hur et al 25 also demonstrated that the levels of wheat-specific IgG1 and IgG4 antibodies were directly correlated with the levels of exposure to wheat and the concentration of wheat dust in the workplace.…”
Section: Discussionsupporting
confidence: 60%